Urinary galectin-3 binding protein (G3BP) as a biomarker for disease activity and renal pathology characteristics in lupus nephritis - Ding, Huihua; Shen, Yiwei; Lin, Cheng; Qin, Ling; He, Shijun; Dai, Min; Okitsu, Shinji L.; DeMartino, Julie A.; Guo, Qiang; Shen, Nan (Arthritis research & therapy, 2022)
There is an urgent need to identify novel biomarkers of LN to reflect renal histological changes. This study aims to investigate urinary G3BP levels in LN patients and their association with renal disease activity both clinically and pathologically. This is a cross-sectional study. A total of 119 lupus nephritis patients were recruited. Thirty patients with chronic kidney diseases (CKD) and 27 healthy volunteers were also recruited as controls. Urinary G3BP was tested by ELISA. Renal histopathology was reviewed by an experienced renal pathologist. Other clinical variables were collected through chart review. The levels of uG3BP were significantly increased in active LN patients compared to those in inactive LN (p<0.001), CKD patients (p=0.01), and healthy controls (p<0.001). ROC analysis indicated a good discrimination ability of uG3BP to differentiate active LN from CKD patients (AUC=0.7), inactive LN (AUC=0.76), or healthy controls (AUC=0.87). uG3BP was positively correlated with SLEDAI (ρ=0.352, p<0.001), rSLEDAI (ρ=0.302, p<0.001), and SLICC RAS (ρ=0.465, p<0.001), indicating a role as a biomarker of disease activity. It also correlated with clinical parameters, including 24-h urine protein, ESR, and serum C3 levels. In patients with 24-h urine protein > 3.0 g/24h, uG3BP levels were higher in proliferative LN than in membranous LN (p=0.04). They could discriminate the two pathogenic types of LN (AUC=0.72), and they also positively correlated with AI (ρ=0.389, p=0.008) and scores of hyaline deposits (ρ=0.418, p=0.006). While in patients with 24-h urine protein ≤ 3.0 g/24h, uG3BP levels were not significantly different between proliferative and membranous LN, and there was no apparent relationship between uG3BP levels with AI or with scores of hyaline deposits, but they correlated positively with scores of cellular/fibrocellular crescents (ρ=0.328, p=0.04). uG3BP is a non-invasive biomarker for clinically and histologically reflecting disease activity. It is associated with active histological changes and can be used as a surrogate biomarker when the renal biopsy is impractical.